July 22nd a window of opportunity for police reform? - Paul Larsson (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article deals with questions concerning the relationship between the Norwegian police reform of 2016 and the terrorist attack at Utøya in 2011. The 2016 reform is often presented as an automatic response to the attack by media, politicians and the Police Director. As something that had to be done. A reform that had been in the cupboard  for more than a decade since the previous reform of 2000 and was simply dusted off and presented as a neat and fresh general solution to many different problems facing the police. The article argues that the terror attack on July 22nd and the subsequent July 22nd Report (The Gjørv Report, NOU 2012:14) presented “a window of opportunity”or police management to make changes not only in the organization of the police, but also in regard to basic ideals of policing. These are changes that would have raised political resistance under normal circumstances. Furthermore, they had little connection to the basic problems of the force as identified in the July 22nd Report and in the debate concerning the police response after the attack.